Flame-retardant elastomer cable material for new energy charging pile and preparation method of flame-retardant elastomer cable material

By preparing a flame-retardant elastomer cable material for new energy charging piles, the problem of poor flame retardancy of polyolefin cable materials is solved, and better flame retardant and mechanical properties are achieved.

CN119505403APending Publication Date: 2025-02-25CHANGZHOU VOCATIONAL INST OF ENG
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411677878.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-22
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The flame retardancy of existing polyolefin cable materials is not good enough, and it is easy to cause droplets and fires at high temperatures.

Method used

Flame-retardant elastomer cable material for new energy charging piles is prepared by mixing low-density polyethylene, ethylene-octene copolymer, cerium trimethylene phosphonate-graphite borosilicate, maleic anhydride grafted polypropylene and additives, and drying, melt blending, extrusion granulation and drying at a specific temperature.

Benefits of technology

It significantly improves the flame retardant performance and mechanical properties of cable materials, and can effectively retardant at high temperatures and prevent fire from occurring.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005147488800000121
    Figure BDA0005147488800000121
  • Figure BDA0005147488800000131
    Figure BDA0005147488800000131
Patent Text Reader

Abstract

The invention relates to the technical field of cable materials, and particularly discloses a flame-retardant elastomer cable material for a new energy charging pile and a preparation method of the flame-retardant elastomer cable material. The flame-retardant elastomer cable material for the new energy charging pile is formed by melting and blending low-density polyethylene, an ethylene-octylene copolymer, boron silicification amino cerium trimethylene phosphonate-graphite, maleic anhydride grafted polypropylene and an auxiliary agent, and matrix resin is the low-density polyethylene and the ethylene-octylene copolymer. The flame-retardant cable material has the advantages of low price, good electrical insulating property, easiness in processing, environmental stress resistance, corrosion resistance and the like, and a good flame-retardant effect is obtained by adding an efficient flame-retardant substance, namely boron silicification amino cerium trimethylene phosphonate-graphite.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of cable materials, and in particular to a flame retardant elastomer cable material for a new energy charging pile and a preparation method thereof. Background Art

[0002] As a device to provide power supplement for new energy vehicles, the total number of new energy charging piles in China has exceeded 10 million so far, and is still growing rapidly. Wires and cables, as carriers of power transmission, are an important part of new energy charging piles. In wires and cables, polymer materials are mainly used for the insulation layer and sheath layer of the cable, which play a role in resisting stress and external environmental influences. At present, the commonly used base material for cables is polyvinyl chloride, but its waste will cause certain pollution to the environment. Polyolefins have the characteristics of being non-toxic, harmless, low-priced, and easy to process and shape, and are expected to gradually replace polyvinyl chloride materials. However, it also has the disadvantage of poor flame retardancy, and is prone to produce molten droplets and ignite at high temperatures, causing fires. Therefore, synergistically improving the flame retardancy and mechanical properties of polyolefin materials is of great significance to the development of wires and cables and new energy charging piles. Summary of the invention

[0003] The purpose of the present invention is to provide a flame retardant elastomer cable material for new energy charging piles and a preparation method thereof, so as to synergistically improve the flame retardancy and mechanical properties of polyolefin materials and solve the problem that ordinary polyolefin cable materials have poor flame retardancy.

[0004] In order to solve the above technical problems, the present invention provides the following technical solutions:

[0005] A method for preparing a flame-retardant elastomer cable material for a new energy charging pile, the preparation method comprising:

[0006] Low-density polyethylene, ethylene-octene copolymer, borosilicate aminotrimethylenephosphonate cerium-graphite, maleic anhydride grafted polypropylene and additives are mixed, dried at 75-85°C for 1-2 hours, melt-blended at 180-200°C, extruded into granules, and dried at 70-90°C for 3-5 hours to obtain a flame-retardant elastomer cable material for new energy charging piles.

[0007] As a limitation of the present invention, the cable material includes, by weight, 80 to 84 parts of high-density polyethylene, 45 to 47 parts of ethylene-octene copolymer, 20 to 24 parts of borosilicate aminotrimethylenephosphonic acid cerium-graphite, 9 to 11 parts of maleic anhydride grafted polypropylene, and 10 to 14 parts of additives.

[0008] As a limitation of the present invention, the preparation method of the borosilicate aminotrimethylenephosphonate cerium-graphite is:

[0009] Mix diphenyldimethoxysilane, phenyltrimethoxysilane, aminotrimethylenephosphonic acid cerium-graphite and anhydrous ethanol, react at 60-70°C for 5-7h, add boric acid in an amount of 0.4-0.6 times the mass of diphenyldimethoxysilane, react at 90-100°C for 5-7h, filter after the reaction, wash with deionized water, and dry at 75-85°C for 3-5h to obtain borosilicate aminotrimethylenephosphonic acid cerium-graphite.

[0010] As a limitation of the present invention, the preparation method of the aminotrimethylenephosphonic acid cerium-graphite is:

[0011] Dissolve aminotrimethylenephosphonic acid in deionized water, stir evenly to obtain an aminotrimethylenephosphonic acid solution, mix the aminotrimethylenephosphonic acid solution, cerium nitrate hexahydrate and deionized water, react at 85-95° C. and 20-40 rpm for 11-13 hours, cool and filter, and dry at 75-85° C. for 3-5 hours to obtain cerium aminotrimethylenephosphonic acid;

[0012] The glacial acetic acid, nitric acid, potassium chlorate and potassium permanganate are uniformly mixed to obtain a mixed acid solution, the natural flake graphite and the mixed acid solution are mixed, and the mixture is reacted at 25-30° C. and 20-40 rpm for 40-60 minutes. After the reaction is completed, the mixture is filtered, washed with deionized water, and dried at 50-60° C. to obtain expandable graphite;

[0013] The expandable graphite and deionized water are mixed and ultrasonically dispersed to obtain a graphite dispersion. The cerium aminotrimethylenephosphonate and the graphite dispersion are mixed in a mass ratio of (0.52-0.53):(49.8-50.2), and the mixture is reacted at 145-155°C for 1-3h. After the reaction is completed, the mixture is filtered, washed with deionized water, and freeze-dried to obtain cerium aminotrimethylenephosphonate-graphite.

[0014] As a limitation of the present invention, the auxiliary agent includes, by weight, 34 to 36 parts of ammonium polyphosphate, 3 to 5 parts of pentaerythritol stearate, 5 to 7 parts of antioxidant, 15 to 17 parts of plasticizer, and 7 to 9 parts of zinc stearate.

[0015] As a limitation of the present invention, the mass ratio of diphenyldimethoxysilane, phenyltrimethoxysilane, aminotrimethylenephosphonic acid cerium-graphite, and anhydrous ethanol is (0.9-1.1):(0.9-1.1):(1.9-2.1):(3.8-4.0).

[0016] As a limitation of the present invention, the mass ratio of the bisphenol A type diether diene to tetrahydrofuran, chloroplatinic acid and tetramethyldisiloxane is (4.9-5.1):(88-90):(1.8-2.0):(0.98-0.99).

[0017] As a limitation of the present invention, the mass ratio of the aminotrimethylenephosphonic acid solution, cerium nitrate hexahydrate and deionized water is (108.96-108.98):(6.73-6.75):(99.5-100.5).

[0018] As a limitation of the present invention, the mass ratio of the natural flake graphite to the mixed acid solution is (1.99-2.01):(26.8-27.2).

[0019] As a limitation of the present invention, the mass ratio of the cerium aminotrimethylenephosphonate to the graphite dispersion is (0.52-0.54):(49.5-50.5).

[0020] Compared with the prior art, the present invention has the following beneficial effects:

[0021] Expandable graphite is a physical intumescent flame retardant. When it burns, expandable graphite releases water vapor and non-flammable gas, which pushes the graphite sheets to pull the distance between the sheets apart, forming a thick porous carbon layer and consuming a lot of heat, thus playing a flame retardant role. However, the density of unmodified expandable graphite itself is small, and the carbon layer produced during the combustion process is easy to detach, reducing the flame retardant effect of the material. Grafting aminotrimethylenephosphonic acid cerium with expandable graphite and wrapping it with a silicon boron resin generated by diphenyldimethoxysilane, phenyltrimethoxysilane and boric acid can further enhance the flame retardant effect of expandable graphite.

[0022] The phosphorus-containing free radicals generated by the aminotrimethylenephosphonic acid cerium complex grafted with expandable graphite during combustion can capture the hydroxyl free radicals generated by the combustion of the polymer. The released non-combustible gas also dilutes the combustible gas generated during the combustion process and the oxygen that the polymer comes into contact with. At the same time, the coke layer generated by the combustion wraps and covers the surface of the expandable graphite, which plays a role in flame retardancy and isolating heat and oxygen.

[0023] The silicon boron resin that wraps the expandable graphite is obtained by reacting diphenyldimethoxysilane, phenyltrimethoxysilane and boric acid. During the combustion process, the silicon dioxide beads generated by the silicon element will cover the carbon layer formed during the combustion of the polymer to prevent further oxidation of the carbon layer, while the boron element will promote the further decomposition of the silicon dioxide beads and further carbonize the carbon layer, making the formed carbon layer more solid and heat-resistant. In addition, during combustion, the silicon boron resin and the aminotrimethylenephosphonic acid cerium complex work together to transform the carbon layer formed during combustion from an independent layer into a mesh cross-linked structure, making the carbon layer denser, thereby enhancing the flame retardant effect. DETAILED DESCRIPTION

[0024] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0025] Low-density polyethylene (2426H) was provided by Sinopec Maoming, ethylene-octene copolymer (8150) was provided by Dow Chemical, USA, ammonium polyphosphate (n=1000) was provided by Jinan Jinyingtai, natural flake graphite (400 mesh) was provided by Shanghai Jiader, antioxidant 1010 (R150166) and DOP plasticizer (R004097) were provided by Shanghai Yien.

[0026] Example 1: A method for preparing a flame-retardant elastomer cable material for a new energy charging pile, specifically:

[0027] Step 1: Preparation of cerium aminotrimethylenephosphonate

[0028] By mass, 8.97 parts of aminotrimethylenephosphonic acid were dissolved in 100 parts of deionized water, and stirred evenly to obtain an aminotrimethylenephosphonic acid solution. The aminotrimethylenephosphonic acid solution, cerium nitrate hexahydrate and deionized water were mixed in a mass ratio of 108.97:6.74:100.0, reacted at 90°C and 30rpm for 12h, cooled and filtered, and dried at 80°C for 4h to obtain cerium aminotrimethylenephosphonate.

[0029] Step 2: Preparation of expandable graphite

[0030] Glacial acetic acid, nitric acid, potassium chlorate and potassium permanganate were uniformly mixed in a mass ratio of 10:12:4:1 to obtain a mixed acid solution, natural flake graphite and the mixed acid solution were mixed in a mass ratio of 2.00:27.0, and reacted at 27°C and 30rpm for 50min. After the reaction was completed, the mixture was filtered, washed with deionized water, and dried at 55°C to obtain expandable graphite.

[0031] Step 3: Preparation of cerium aminotrimethylenephosphonate-graphite

[0032] By mass, 1 part of expandable graphite and 500 parts of deionized water were mixed and ultrasonically dispersed to obtain a graphite dispersion. Aminotrimethylenephosphonic acid cerium and graphite dispersion were mixed in a mass ratio of 0.525:50, and reacted at 150° C. for 2 h. After the reaction was completed, the mixture was filtered, washed with deionized water, and freeze-dried to obtain aminotrimethylenephosphonic acid cerium-graphite.

[0033] Step 4: Preparation of borosilicate aminotrimethylenephosphonate cerium-graphite

[0034] Diphenyldimethoxysilane, phenyltrimethoxysilane, aminotrimethylenephosphonic acid cerium-graphite and anhydrous ethanol were mixed in a mass ratio of 1.0:1.0:2.0:3.9, reacted at 65°C for 6 hours, added with boric acid 0.5 times the mass of diphenyldimethoxysilane, reacted at 95°C for 6 hours, filtered after the reaction was completed, washed with deionized water, and dried at 80°C for 4 hours to obtain borosilicate aminotrimethylenephosphonic acid cerium-graphite.

[0035] Step 5: Prepare the additive

[0036] By weight, 35 parts of ammonium polyphosphate, 4 parts of pentaerythritol stearate, 6 parts of antioxidant 1010, 16 parts of DOP plasticizer, and 8 parts of zinc stearate were uniformly mixed to obtain an auxiliary agent.

[0037] Step 6: Preparation of flame-retardant elastomer cable material for new energy charging piles

[0038] By mass, 82 parts of low-density polyethylene, 46 parts of ethylene-octene copolymer, 22 parts of borosilicate aminotrimethylenephosphonate cerium-graphite, 10 parts of maleic anhydride grafted polypropylene, and 12 parts of additives were mixed, dried at 80°C for 1.5 hours, melt-blended at 190°C, extruded into granules, and dried at 80°C for 4 hours to obtain a flame-retardant elastomer cable material for new energy charging piles.

[0039] Embodiment 2: A method for preparing a flame retardant elastomer cable material for a new energy charging pile, specifically:

[0040] Step 1: Preparation of cerium aminotrimethylenephosphonate

[0041] By mass, 8.97 parts of aminotrimethylenephosphonic acid were dissolved in 100 parts of deionized water, and stirred evenly to obtain an aminotrimethylenephosphonic acid solution. The aminotrimethylenephosphonic acid solution, cerium nitrate hexahydrate and deionized water were mixed in a mass ratio of 108.97:6.74:100.0, reacted at 90°C and 30rpm for 12h, cooled and filtered, and dried at 80°C for 4h to obtain cerium aminotrimethylenephosphonate.

[0042] Step 2: Preparation of expandable graphite

[0043] Glacial acetic acid, nitric acid, potassium chlorate and potassium permanganate were uniformly mixed in a mass ratio of 10:12:4:1 to obtain a mixed acid solution, natural flake graphite and the mixed acid solution were mixed in a mass ratio of 2.00:27.0, and reacted at 27°C and 30rpm for 50min. After the reaction was completed, the mixture was filtered, washed with deionized water, and dried at 55°C to obtain expandable graphite.

[0044] Step 3: Preparation of cerium aminotrimethylenephosphonate-graphite

[0045] By mass, 1 part of expandable graphite and 500 parts of deionized water were mixed and ultrasonically dispersed to obtain a graphite dispersion. Aminotrimethylenephosphonic acid cerium and graphite dispersion were mixed in a mass ratio of 0.525:50, and reacted at 150° C. for 2 h. After the reaction was completed, the mixture was filtered, washed with deionized water, and freeze-dried to obtain aminotrimethylenephosphonic acid cerium-graphite.

[0046] Step 4: Preparation of borosilicate aminotrimethylenephosphonate cerium-graphite

[0047] Diphenyldimethoxysilane, phenyltrimethoxysilane, aminotrimethylenephosphonic acid cerium-graphite and anhydrous ethanol were mixed in a mass ratio of 1.0:1.0:2.0:3.9, reacted at 65°C for 6 hours, added with boric acid 0.5 times the mass of diphenyldimethoxysilane, reacted at 95°C for 6 hours, filtered after the reaction was completed, washed with deionized water, and dried at 80°C for 4 hours to obtain borosilicate aminotrimethylenephosphonic acid cerium-graphite.

[0048] Step 5: Prepare the additive

[0049] By weight, 35 parts of ammonium polyphosphate, 4 parts of pentaerythritol stearate, 6 parts of antioxidant 1010, 16 parts of DOP plasticizer, and 8 parts of zinc stearate were uniformly mixed to obtain an auxiliary agent.

[0050] Step 6: Preparation of flame-retardant elastomer cable material for new energy charging piles

[0051] By mass, 80 parts of low-density polyethylene, 45 parts of ethylene-octene copolymer, 20 parts of borosilicate aminotrimethylenephosphonate cerium-graphite, 9 parts of maleic anhydride grafted polypropylene, and 10 parts of additives were mixed, dried at 80°C for 1.5 hours, melt-blended at 190°C, extruded into granules, and dried at 80°C for 4 hours to obtain a flame-retardant elastomer cable material for new energy charging piles.

[0052] Embodiment 3: A method for preparing a flame retardant elastomer cable material for a new energy charging pile, specifically:

[0053] Step 1: Preparation of cerium aminotrimethylenephosphonate

[0054] By mass, 8.97 parts of aminotrimethylenephosphonic acid were dissolved in 100 parts of deionized water, and stirred evenly to obtain an aminotrimethylenephosphonic acid solution. The aminotrimethylenephosphonic acid solution, cerium nitrate hexahydrate and deionized water were mixed in a mass ratio of 108.97:6.74:100.0, reacted at 90°C and 30rpm for 12h, cooled and filtered, and dried at 80°C for 4h to obtain cerium aminotrimethylenephosphonate.

[0055] Step 2: Preparation of expandable graphite

[0056] Glacial acetic acid, nitric acid, potassium chlorate and potassium permanganate were uniformly mixed in a mass ratio of 10:12:4:1 to obtain a mixed acid solution, natural flake graphite and the mixed acid solution were mixed in a mass ratio of 2.00:27.0, and reacted at 27°C and 30rpm for 50min. After the reaction was completed, the mixture was filtered, washed with deionized water, and dried at 55°C to obtain expandable graphite.

[0057] Step 3: Preparation of cerium aminotrimethylenephosphonate-graphite

[0058] By mass, 1 part of expandable graphite and 500 parts of deionized water were mixed and ultrasonically dispersed to obtain a graphite dispersion. Aminotrimethylenephosphonic acid cerium and graphite dispersion were mixed in a mass ratio of 0.525:50, and reacted at 150° C. for 2 h. After the reaction was completed, the mixture was filtered, washed with deionized water, and freeze-dried to obtain aminotrimethylenephosphonic acid cerium-graphite.

[0059] Step 4: Preparation of borosilicate aminotrimethylenephosphonate cerium-graphite

[0060] Diphenyldimethoxysilane, phenyltrimethoxysilane, aminotrimethylenephosphonic acid cerium-graphite and anhydrous ethanol were mixed in a mass ratio of 1.0:1.0:2.0:3.9, reacted at 65°C for 6 hours, added with boric acid 0.5 times the mass of diphenyldimethoxysilane, reacted at 95°C for 6 hours, filtered after the reaction was completed, washed with deionized water, and dried at 80°C for 4 hours to obtain borosilicate aminotrimethylenephosphonic acid cerium-graphite.

[0061] Step 5: Prepare the additive

[0062] By weight, 35 parts of ammonium polyphosphate, 4 parts of pentaerythritol stearate, 6 parts of antioxidant 1010, 16 parts of DOP plasticizer, and 8 parts of zinc stearate were uniformly mixed to obtain an auxiliary agent.

[0063] Step 6: Preparation of flame-retardant elastomer cable material for new energy charging piles

[0064] By mass, 84 parts of low-density polyethylene, 47 parts of ethylene-octene copolymer, 24 parts of borosilicate aminotrimethylenephosphonate cerium-graphite, 11 parts of maleic anhydride grafted polypropylene, and 14 parts of additives were mixed, dried at 80°C for 1.5 hours, melt-blended at 190°C, extruded into granules, and dried at 80°C for 4 hours to obtain a flame-retardant elastomer cable material for new energy charging piles.

[0065] Based on Example 1, control experiments were carried out, specifically Comparative Example 1, Comparative Example 2 and Comparative Example 3, as described below:

[0066] Comparative Example 1: The surface of cerium aminotrimethylenephosphonate-graphite was not subjected to borosilicate treatment, and other conditions were the same as those in Example 1.

[0067] A method for preparing a flame retardant elastomer cable material for a new energy charging pile, specifically comprising:

[0068] Step 1: Preparation of cerium aminotrimethylenephosphonate

[0069] By mass, 8.97 parts of aminotrimethylenephosphonic acid were dissolved in 100 parts of deionized water, and stirred evenly to obtain an aminotrimethylenephosphonic acid solution. The aminotrimethylenephosphonic acid solution, cerium nitrate hexahydrate and deionized water were mixed in a mass ratio of 108.97:6.74:100.0, reacted at 90°C and 30rpm for 12h, cooled and filtered, and dried at 80°C for 4h to obtain cerium aminotrimethylenephosphonate.

[0070] Step 2: Preparation of expandable graphite

[0071] Glacial acetic acid, nitric acid, potassium chlorate and potassium permanganate were uniformly mixed in a mass ratio of 10:12:4:1 to obtain a mixed acid solution, natural flake graphite and the mixed acid solution were mixed in a mass ratio of 2.00:27.0, and reacted at 27°C and 30rpm for 50min. After the reaction was completed, the mixture was filtered, washed with deionized water, and dried at 55°C to obtain expandable graphite.

[0072] Step 3: Preparation of cerium aminotrimethylenephosphonate-graphite

[0073] By mass, 1 part of expandable graphite and 500 parts of deionized water were mixed and ultrasonically dispersed to obtain a graphite dispersion. Aminotrimethylenephosphonic acid cerium and graphite dispersion were mixed in a mass ratio of 0.525:50, and reacted at 150° C. for 2 h. After the reaction was completed, the mixture was filtered, washed with deionized water, and freeze-dried to obtain aminotrimethylenephosphonic acid cerium-graphite.

[0074] Step 4: Prepare the additive

[0075] By weight, 35 parts of ammonium polyphosphate, 4 parts of pentaerythritol stearate, 6 parts of antioxidant 1010, 16 parts of DOP plasticizer, and 8 parts of zinc stearate were uniformly mixed to obtain an auxiliary agent.

[0076] Step 5: Preparation of flame-retardant elastomer cable material for new energy charging piles

[0077] By mass, 82 parts of low-density polyethylene, 46 parts of ethylene-octene copolymer, 22 parts of aminotrimethylenephosphonic acid cerium-graphite, 10 parts of maleic anhydride grafted polypropylene, and 12 parts of additives were mixed, dried at 80°C for 1.5 hours, melt blended at 190°C, extruded into granules, and dried at 80°C for 4 hours to obtain a flame retardant elastomer cable material for new energy charging piles.

[0078] Comparative Example 2: No cerium aminotrimethylenephosphonate was added, and the remaining conditions were the same as those in Example 1.

[0079] A method for preparing a flame retardant elastomer cable material for a new energy charging pile, specifically comprising:

[0080] Step 1: Preparation of expandable graphite

[0081] Glacial acetic acid, nitric acid, potassium chlorate and potassium permanganate were uniformly mixed in a mass ratio of 10:12:4:1 to obtain a mixed acid solution, natural flake graphite and the mixed acid solution were mixed in a mass ratio of 2.00:27.0, and reacted at 27°C and 30rpm for 50min. After the reaction was completed, the mixture was filtered, washed with deionized water, and dried at 55°C to obtain expandable graphite.

[0082] Step 2: Preparation of borosilicate expandable graphite

[0083] Diphenyldimethoxysilane, phenyltrimethoxysilane, expandable graphite and anhydrous ethanol were mixed in a mass ratio of 1.0:1.0:2.0:3.9, reacted at 65°C for 6 hours, added with boric acid in an amount 0.5 times the mass of diphenyldimethoxysilane, reacted at 95°C for 6 hours, filtered after the reaction was completed, washed with deionized water, and dried at 80°C for 4 hours to obtain borosilicate expandable graphite.

[0084] Step 3: Prepare the additive

[0085] By weight, 35 parts of ammonium polyphosphate, 4 parts of pentaerythritol stearate, 6 parts of antioxidant 1010, 16 parts of DOP plasticizer, and 8 parts of zinc stearate were uniformly mixed to obtain an auxiliary agent.

[0086] Step 4: Preparation of flame-retardant elastomer cable material for new energy charging piles

[0087] By mass, 82 parts of low-density polyethylene, 46 parts of ethylene-octene copolymer, 22 parts of borosilicate expandable graphite, 10 parts of maleic anhydride grafted polypropylene, and 12 parts of additives were mixed, dried at 80°C for 1.5 hours, melt blended at 190°C, extruded into granules, and dried at 80°C for 4 hours to obtain a flame retardant elastomer cable material for new energy charging piles.

[0088] Comparative Example 3: Cerium aminotrimethylenephosphonate was directly added, and the remaining conditions were the same as those in Example 1.

[0089] A method for preparing a flame retardant elastomer cable material for a new energy charging pile, specifically comprising:

[0090] Step 1: Preparation of cerium aminotrimethylenephosphonate

[0091] By mass, 8.97 parts of aminotrimethylenephosphonic acid were dissolved in 100 parts of deionized water, and stirred evenly to obtain an aminotrimethylenephosphonic acid solution. The aminotrimethylenephosphonic acid solution, cerium nitrate hexahydrate and deionized water were mixed in a mass ratio of 108.97:6.74:100.0, reacted at 90°C and 30rpm for 12h, cooled and filtered, and dried at 80°C for 4h to obtain cerium aminotrimethylenephosphonate.

[0092] Step 2: Prepare the additive

[0093] By weight, 35 parts of ammonium polyphosphate, 4 parts of pentaerythritol stearate, 6 parts of antioxidant 1010, 16 parts of DOP plasticizer, and 8 parts of zinc stearate were uniformly mixed to obtain an auxiliary agent.

[0094] Step 3: Preparation of flame-retardant elastomer cable material for new energy charging piles

[0095] By mass, 82 parts of low-density polyethylene, 46 parts of ethylene-octene copolymer, 22 parts of cerium aminotrimethylene phosphonate, 10 parts of maleic anhydride grafted polypropylene, and 12 parts of additives were mixed, dried at 80°C for 1.5 hours, melt blended at 190°C, extruded into granules, and dried at 80°C for 4 hours to obtain flame-retardant elastomer cable materials for new energy charging piles.

[0096] Detection experiment:

[0097] The flame retardant elastomer cable material for the new energy charging pile required for the test was prepared according to the preparation methods in Example 1, Example 2, Example 3, Comparative Example 1, Comparative Example 2, and Comparative Example 3 respectively.

[0098] Mechanical properties test: According to "Determination of Tensile Properties of Plastics" (GB / T 1040-2006), a mechanical punching machine is used to punch out the Type II specimens (115mm×25mm) required for the test on the cable material prepared above, and the specimens are fixed on the fixture of the tensile testing machine. The tensile testing machine is used to test each specimen in turn, and the tensile strength and elongation at break of each specimen are measured.

[0099] Vertical burning test: According to the “Test method for combustion performance of rigid foam plastics - Vertical burning method” (GB / T 8333-2008), a sample of 100 mm × 13 mm was cut from the cable material prepared above, and the sample was conditioned in an environment of 23°C and 50% humidity for 24 hours. A vertical burning test was performed using a CZF-3 horizontal / vertical burning tester, and the evaluation standard was UL-94.

[0100] UL-94 vertical burning rating standard

[0101]

[0102] Volume resistivity test: According to the "Test Method for Volume Resistivity and Surface Resistivity of Solid Insulating Materials" (GB / T1410-2006), a 100mm×100mm sample was cut from the above cable material and tested using a ZC-90 series high insulation resistance meter. The inner electrode area was 19.63cm2, the average thickness of the sample was 1mm, and the test voltage was 500V.

[0103]

[0104] Conclusion: It can be seen from the experiment that the sample of Example 1 is better than the samples of Comparative Example 1, Comparative Example 2 and Comparative Example 3 in each test, indicating that the cable material prepared in Example 1 is better than the cable materials prepared in Comparative Example 1, Comparative Example 2 and Comparative Example 3 in terms of mechanical properties and flame retardancy, and effectively improves the problem that the flame retardancy of ordinary polyolefin cable materials is not good enough.

[0105] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.

Claims

1. A method for preparing a flame-retardant elastomer cable material for a new energy charging pile, characterized in that: The preparation method is: Low-density polyethylene, ethylene-octene copolymer, borosilicate aminotrimethylenephosphonate cerium-graphite, maleic anhydride grafted polypropylene and additives are mixed, dried at 75-85°C for 1-2 hours, melt-blended at 180-200°C, extruded into granules, and dried at 70-90°C for 3-5 hours to obtain a flame-retardant elastomer cable material for new energy charging piles.

2. The method for preparing a flame-retardant elastomer cable material for a new energy charging pile according to claim 1, characterized in that: Calculated by weight, the cable material comprises 80-84 parts of high-density polyethylene, 45-47 parts of ethylene-octene copolymer, 20-24 parts of borosilicate aminotrimethylenephosphonic acid cerium-graphite, 9-11 parts of maleic anhydride grafted polypropylene, and 10-14 parts of additives.

3. A method for preparing a flame-retardant elastomer cable material for a new energy charging pile according to claim 1 or claim 2, characterized in that: The preparation method of borosilicate aminotrimethylenephosphonic acid cerium-graphite is: Mix diphenyldimethoxysilane, phenyltrimethoxysilane, aminotrimethylenephosphonic acid cerium-graphite and anhydrous ethanol, react at 60-70°C for 5-7h, add boric acid in an amount of 0.4-0.6 times the mass of diphenyldimethoxysilane, react at 90-100°C for 5-7h, filter after the reaction, wash with deionized water, and dry at 75-85°C for 3-5h to obtain borosilicate aminotrimethylenephosphonic acid cerium-graphite.

4. The method for preparing a flame-retardant elastomer cable material for a new energy charging pile according to claim 3, characterized in that: The preparation method of aminotrimethylenephosphonic acid cerium-graphite is: Dissolve aminotrimethylenephosphonic acid in deionized water, stir evenly to obtain an aminotrimethylenephosphonic acid solution, mix the aminotrimethylenephosphonic acid solution, cerium nitrate hexahydrate and deionized water, react at 85-95° C. and 20-40 rpm for 11-13 hours, cool and filter, and dry at 75-85° C. for 3-5 hours to obtain cerium aminotrimethylenephosphonic acid; The glacial acetic acid, nitric acid, potassium chlorate and potassium permanganate are uniformly mixed to obtain a mixed acid solution, the natural flake graphite and the mixed acid solution are mixed, and the mixture is reacted at 25-30° C. and 20-40 rpm for 40-60 minutes. After the reaction is completed, the mixture is filtered, washed with deionized water, and dried at 50-60° C. to obtain expandable graphite; The expandable graphite and deionized water are mixed and ultrasonically dispersed to obtain a graphite dispersion. The cerium aminotrimethylenephosphonate and the graphite dispersion are mixed in a mass ratio of (0.52-0.53):(49.8-50.2), and the mixture is reacted at 145-155°C for 1-3h. After the reaction is completed, the mixture is filtered, washed with deionized water, and freeze-dried to obtain cerium aminotrimethylenephosphonate-graphite.

5. A method for preparing a flame-retardant elastomer cable material for a new energy charging pile according to claim 1 or claim 2, characterized in that: Calculated by weight, the additives include 34 to 36 parts of ammonium polyphosphate, 3 to 5 parts of pentaerythritol stearate, 5 to 7 parts of antioxidant, 15 to 17 parts of plasticizer, and 7 to 9 parts of zinc stearate.

6. The method for preparing a flame-retardant elastomer cable material for a new energy charging pile according to claim 3, characterized in that: The mass ratio of diphenyldimethoxysilane, phenyltrimethoxysilane, aminotrimethylenephosphonic acid cerium-graphite and anhydrous ethanol is (0.9-1.1):(0.9-1.1):(1.9-2.1):(3.8-4.0).

7. The method for preparing a flame-retardant elastomer cable material for a new energy charging pile according to claim 4, characterized in that: The mass ratio of aminotrimethylenephosphonic acid solution, cerium nitrate hexahydrate and deionized water is (108.96-108.98):(6.73-6.75):(99.5-100.5).

8. The method for preparing a flame-retardant elastomer cable material for a new energy charging pile according to claim 4, characterized in that: The mass ratio of natural flake graphite and mixed acid solution is (1.99-2.01):(26.8-27.2).

9. The method for preparing a flame-retardant elastomer cable material for a new energy charging pile according to claim 4, characterized in that: The mass ratio of cerium aminotrimethylenephosphonate to graphite dispersion is (0.52-0.54):(49.5-50.5).